Wearable SERS (Surface Enhanced Raman Scattering) sensor with asymmetric Janus structure as well as preparation method and application of wearable SERS sensor

By using a wearable SERS sensor with an asymmetric Janus structure, combined with humidity-responsive hydrogel and functionalized nanocomposite materials, the contradictions of traditional SERS sensors in terms of flexibility, uniform signal distribution, and long-term stability have been resolved. This enables non-invasive, dynamic monitoring of trace metabolites in tears, breaking through the limitations of traditional detection methods and making it suitable for early diagnosis of glaucoma.

CN121141618APending Publication Date: 2025-12-16FUJIAN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511315616.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

Existing SERS sensors have contradictions in terms of flexibility, uniform signal distribution, and long-term stability, making it difficult to achieve non-invasive, dynamic monitoring of trace metabolites in tears. Furthermore, traditional detection methods are cumbersome to operate and have high detection limits, failing to meet the needs of early glaucoma diagnosis.

Method used

A wearable SERS sensor with an asymmetric Janus structure, combined with humidity-responsive hydrogels and functionalized nanocomposites, is prepared through photopolymerization and spin coating processes to form an adhesion layer and a detection layer. This solves the problems of nanoparticle deactivation and signal inhomogeneity, achieving high adsorption rate and high sensitivity detection.

Benefits of technology

It achieves high sensitivity (detection limit as low as 0.027μM), high stability (RSD≤7.63%) and high cell viability (>95%), making it suitable for early glaucoma screening and personalized diagnosis and treatment of chronic diseases, and has the potential for clinical translation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121141618A_ABST
    Figure CN121141618A_ABST
Patent Text Reader

Abstract

The invention discloses a wearable SERS (Surface Enhanced Raman Scattering) sensor with an asymmetric Janus structure as well as a preparation method and application of the wearable SERS sensor. According to the sensor, an asymmetric double-layer structure is constructed through ultraviolet polymerization and a spin-coating technology, an adhesion layer (AA / HACC hydrogel) has humidity responsiveness and high adhesion, and a detection layer (CCNF / Au NCs) inhibits a coffee ring effect and ensures uniform distribution of nanoparticles. The detection limit of the hydrogel is as low as 0.027 [mu] M (L-phenylalanine), the RSD is less than or equal to 7.63%, the cell survival rate is greater than 95%, and these results jointly prove the excellent performance of the hydrogel in the aspects of sensitivity and stability. In addition, due to the characteristic of rapid preparation through photopolymerization, large-scale production can be realized. Therefore, the asymmetric Janus-SERS hydrogel sensor is suitable for early screening of glaucoma, dynamic monitoring of tear metabolites and personalized diagnosis and treatment of chronic diseases, has high sensitivity, biocompatibility and antibacterial performance, and has clinical transformation potential.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of biomedical detection, and particularly relates to a preparation method and application of a wearable sensor with an asymmetric Janus structure based on surface-enhanced Raman scattering (SERS). BACKGROUND

[0002] Glaucoma is the leading cause of irreversible blindness worldwide, and its pathological feature is the progressive loss of retinal ganglion cells and optic nerve damage, which is closely related to chronic oxidative stress and metabolic disorders in the eye. Studies have shown that changes in the concentrations of N-acetyl-L-cysteine, uridine, L-phenylalanine and other metabolites in tears are key biomarkers for early diagnosis of glaucoma. However, existing detection techniques (such as nuclear magnetic resonance spectroscopy and liquid chromatography) rely on invasive sampling (aqueous humor or blood) and complex instruments, making it difficult to achieve non-invasive and dynamic monitoring. In addition, the detection limit of traditional methods is relatively high (usually in the micromolar level), which cannot meet the precise analysis needs of trace metabolites, and the operation process is cumbersome, making it difficult to promote in clinical practice.

[0003] In recent years, surface-enhanced Raman scattering (SERS) technology has shown great potential in biomarker analysis due to its single-molecule-level detection capability. SERS significantly amplifies molecular vibration signals through the localized surface plasmon resonance effect (LSPR) of noble metal nanostructures (such as gold and silver nanoparticles), and has advantages such as no need for labeling, resistance to photobleaching, and fast response. However, traditional SERS sensors mostly use rigid materials (such as silicon wafers and glass), which still have problems such as insufficient mechanical performance, poor signal uniformity, and complex preparation process. To overcome these limitations, flexible SERS sensors have gradually become a hot topic. For example, polydimethylsiloxane (PDMS) based sensors have a certain flexibility, but their low light transmittance and significant background scattering interference are significant; cellulose nanofiber (CCNF) composites can inhibit the "coffee ring effect" by controlling the solvent evaporation path, but lack dynamic response capability and cannot optimize the distance between nanoparticles to enhance the signal in real time. Existing flexible sensors mostly use single functional layer design, which makes it difficult to achieve efficient molecule enrichment, dynamic signal regulation, and anti-interference detection at the same time.

[0004] Hydrogels are considered ideal wearable sensor substrates due to their three-dimensional network structure, high light transmittance, and humidity response characteristics. However, a single hydrogel layer still faces two major challenges - the "coffee ring effect" and nanoparticle stability. The "coffee ring effect" refers to the phenomenon that when a droplet containing solute (such as coffee, ink, or nanoparticle suspension) evaporates on a solid surface, the solute forms an uneven ring-shaped deposit at the edge of the droplet, causing inaccurate detection.

[0005] Publication No. CN118109563A discloses a LoC-SERS platform for detecting Parkinson's disease markers, which has high sensitivity and strong specificity for detecting Parkinson's disease markers; and the assembly process is simple and the detection speed is fast. Publication No. CN114034682A discloses a preparation method of an ultrathin skin / glove-based wearable SERS sensor. The sensor can realize high-sensitivity quantitative detection in actual application. The in-situ pesticide detection method has high feasibility, high efficiency, strong stability, and can detect 10 ppt of pesticide thiram. The uniqueness of the application scenario further highlights the clinical value of the invention. Existing SERS sensors are mainly focused on in vitro diagnosis (CN118109563A) or skin contact detection (CN114034682A). The present application first expands non-invasive dynamic monitoring to the field of tear metabolites, providing an irreplaceable technical means for early screening of chronic diseases such as glaucoma. SUMMARY

[0006] To solve the problems in the prior art, the present application provides a wearable SERS sensor with an asymmetric Janus structure and a preparation method and application thereof. By introducing an asymmetric Janus structure, the present application combines humidity-responsive hydrogel with functionalized nanocomposites, effectively avoiding the deactivation of acrylic hydrogel on nanoparticles while maintaining the high adhesion and flexibility of wearable sensors, and balancing high adsorption rate and high sensitive SERS signal, thereby breaking through the inherent contradiction between traditional SERS technology in flexibility, signal distribution uniformity and long-term stability, and providing an innovative solution for non-invasive, high-precision dynamic monitoring of early diagnosis of glaucoma.

[0007] To achieve the above-mentioned purpose, the present application realizes the following technical solutions: One of the purposes of the present application is to provide a wearable SERS sensor with an asymmetric Janus structure, which is composed of an adhesion layer and a detection layer. The adhesion layer is an acrylic / hydroxypropyltrimethylammonium chloride chitosan hydrogel with a thickness of 53-147 mm. The detection layer is a gold nanocube-cationic cellulose nanofiber.

[0008] The second purpose of the present application is to provide a preparation method of a wearable SERS sensor with an asymmetric Janus structure, which comprises the following steps: (1) Preparation of the adhesion layer: Mix acrylic acid and hydroxypropyltrimethylammonium chloride chitosan, add a crosslinking agent and a photoinitiator, and stir thoroughly to prepare a prepolymer solution. Transfer the prepolymer solution to a mold and irradiate it with ultraviolet light to form an acrylic acid / hydroxypropyltrimethylammonium chloride chitosan hydrogel adhesion layer. (2) Preparation of the detection layer: After stirring the HAuCl4 solution, the cetyltrimethylammonium bromide solution and the ultrapure water uniformly, the NaBH4 solution is added, and after mixing uniformly, the gold seed solution is prepared by standing. After dilution of the gold seed solution, the growth solution prepared by ultrapure water, cetyltrimethylammonium bromide, HAuCl4 and ascorbic acid is added, and the gold nanocubes are generated by standing. The cetyltrimethylammonium bromide is removed by centrifugation, and the purified gold nanocube solution is obtained by washing with ultrapure water. The cetyltrimethylammonium bromide is removed by centrifugation and concentration of the gold nanocube solution, and the gold nanocube-cationic cellulose nanofiber detection layer is prepared by mixing with the cationic cellulose nanofiber. (3) Janus structure assembly: the gold nanocube-cationic cellulose nanofiber detection layer is spin-coated on the surface of the acrylic acid / hydroxypropyltrimethylammonium chloride chitosan hydrogel adhesion layer to form a wearable SERS sensor with an asymmetric Janus structure.

[0009] Further, the mass ratio of the acrylic acid and the hydroxypropyltrimethylammonium chloride chitosan is 2:1.

[0010] Further, the concentration of the hydroxypropyltrimethylammonium chloride chitosan is 1% to 3%.

[0011] Further, the crosslinking agent is N,N'-methylenebisacrylamide, and the concentration is 2%, accounting for 2.5% of the mass of the acrylic acid.

[0012] Further, the photoinitiator is 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide, and the concentration is 1%, accounting for 2.5% of the mass of the acrylic acid.

[0013] Further, the concentration of the cationic cellulose nanofiber is 0.1% to 0.9%.

[0014] The third object of the present application is to provide an application of the wearable SERS sensor with an asymmetric Janus structure in the field of non-invasive tear metabolite monitoring.

[0015] Compared with the prior art, the present application has the following advantages and beneficial effects: 1、Although wearable hydrogel sensors have been widely used in biological monitoring, in the field of SERS detection, due to the presence of various strong acidic groups in acrylic acid and its polymer system, non-specific interaction with metal nanoparticles easily occurs, inducing aggregation of nanoparticles at the hydrogel interface, resulting in a decrease in "hot spots", particle inactivation and Raman signal attenuation. The present application introduces an asymmetric Janus structure, which combines humidity-responsive hydrogel with functionalized nanocomposites on the surface, effectively avoiding the inactivation of nanoparticles by acrylic acid hydrogel while maintaining high adhesion and flexibility of wearable sensors, balancing high adsorption rate and high sensitive SERS signal, thereby breaking the inherent contradiction between traditional SERS technology in flexibility, signal distribution uniformity and long-term stability. The detection limit of the present application is as low as 0.027 μM, RSD≤7.63%, and the cell survival rate is >95%, showing excellent sensitivity and stability. The preparation method combines photopolymerization and spin coating process, which has the advantages of rapidness and scalability.

[0016] 2、The cationic cellulose nanofiber introduced in the present application not only solves the "coffee ring effect" commonly seen in spin coating technology, but also forms a stable support network for nanoparticles in the interface layer, significantly improving signal uniformity and long-term stability. The introduction of acrylic acid can improve the adhesion of SERS sensors, hydrophilicity, excellent biocompatibility and high swelling rate, adapt to the need to meet the human mechanics of the fit to collect the tear fluid on the curved surface of the eye, realize the efficient, non-invasive and in-situ dynamic monitoring of various biomarkers such as N-acetyl-L-cysteine, uridine, L-phenylalanine and glycine in tear fluid, suitable for early screening of glaucoma and personalized diagnosis and treatment of chronic diseases, and has clinical transformation potential. BRIEF DESCRIPTION OF DRAWINGS

[0017] Figure 1 Raman spectra and Raman signal intensity of wearable SERS sensors with asymmetric Janus structure prepared by different concentrations of cationic cellulose nanofiber (HACC) in Example 2; Figure 2 SERS spectra and corresponding Raman signal intensity of wearable SERS sensors with asymmetric Janus structure prepared by different concentrations of hydroxypropyl trimethyl ammonium chloride chitosan (CCNF) in Example 3; Figure 3 Sensitivity and linear response of wearable SERS sensors with asymmetric Janus structure in Example 4 in the detection of various tear metabolites; Figure 4 Sensitivity and recovery rate evaluation of wearable SERS sensors with asymmetric Janus structure in Example 4 in the detection of various metabolites in artificial tears; Figure 5Example 5 wearable SERS sensor with asymmetric Janus structure for safety performance evaluation. DETAILED DESCRIPTION

[0018] The application is further described in connection with the preferred embodiments, and it is to be understood that the described endpoints of the ranges of the disclosed application and any value described herein are not to be construed to be precise limits, and that these ranges and values are to be understood to encompass values close thereto; and that the endpoints of the various ranges of values, the endpoints of the ranges of values and individual values between the endpoints of the ranges of values, and the individual values themselves, can be combined with one another to form one or more new ranges of values, which are to be considered as being expressly disclosed herein; The materials, reagents and the like used in the following examples are commercially available unless otherwise specified; The experimental methods used in the following examples are conventional unless otherwise specified. In the following examples, the wearable SERS sensor with asymmetric Janus structure is referred to as asymmetric Janus-SERS sensor.

[0019] Example 1 The present embodiment provides a preparation method of a wearable SERS sensor with asymmetric Janus structure, comprising the following steps: (1) Preparation of the adhesion layer: weigh acrylic acid and hydroxypropyl trimethyl ammonium chloride chitosan with a concentration of 2%, and mix them in a mass ratio of 2:1. Add N,N'-methylenebisacrylamide as a crosslinking agent to the mixture, with a concentration of 2.5% of the mass of acrylic acid, and 2,4,6-trimethylbenzoyl-diphenyl phosphine oxide (TPO) as a photoinitiator, with a concentration of 2.5% of the mass of acrylic acid, and stir well to mix them evenly; transfer the obtained adhesion layer solution to a polytetrafluoroethylene mold, and irradiate it with 365 nm ultraviolet light for 5 minutes to prepare an acrylic acid / hydroxypropyl trimethyl ammonium chloride chitosan adhesion layer. The thickness of the adhesion layer is 89 mm after detection; (2) Preparation of the detection layer: Add 103 μL of 1wt% HAuCl4 solution, 7.5 mL of 100 mM hexadecyl trimethyl ammonium bromide solution and 2.4 mL of ultrapure water into the reaction container, stir at 35℃, then quickly stir 0.6 mL of 10 mM NaBH4 solution into the container, then let it stand for 2 hours to obtain a gold seed solution; dilute the gold seed solution by 100 times, add 18 μL of the diluted gold seed solution into a growth solution made of 21 mL of ultrapure water, 4 mL of 100 mM hexadecyl trimethyl ammonium bromide solution, 205 μL of 1wt% HAuCl4 solution and 1.5 mL of 100 mM acrylic acid solution, then stand for 6 h in a reaction container at 35℃ to obtain a 60 nm gold nanocube solution; wherein the 60 nm gold nanocube solution is centrifuged at 4000 rpm for 10 min and washed twice with ultrapure water for the preparation of the detection layer; Take 1 mL of the gold nanocube solution prepared above into a centrifuge tube, and centrifuge again to remove hexadecyl trimethyl ammonium bromide in the solution, with a concentration ratio of 10 times; add 100 μL of 0.7% hydroxypropyl trimethyl ammonium chloride chitosan solution to the gold nanocube precipitate after centrifugation, and mix uniformly by gentle vortex to obtain a gold nanocube-cationic cellulose nanofiber solution, which is the detection layer; (3) Janus structure assembly: take 10 μL of the prepared uniformly dispersed gold nanocube-cationic cellulose nanofiber solution, and coat it on the surface of a circular acrylic acid / hydroxypropyl trimethyl ammonium chloride chitosan adhesive layer with a size of 0.2 x 0.2 cm² by spin coating technology with a spin coating cycle of 2, to form an asymmetric Janus-SERS sensor.

[0020] Example 2 The difference between Example 2 and Example 1 is that the concentration of cationic cellulose nanofiber HACC used in step (1) of Example 2 is 1%, 1.5%, 2.5% and 3%, and the rest of the preparation method is the same as that of Example 1.

[0021] The asymmetric Janus-SERS sensors prepared with the above concentrations were detected for Raman signal intensity, and the results are shown in Figure 1 As shown, the asymmetric Janus-SERS sensors prepared with cationic cellulose nanofiber HACC concentrations of 1% to 3% all have strong Raman signals, and the Raman signal is strongest when the concentration of cationic cellulose nanofiber HACC is 2%.

[0022] Example 3 The difference between Example 3 and Example 1 is that the concentration of hydroxypropyltrimethylammonium chloride chitosan CCNF used in step (4) of Example 3 is 0.1%, 0.3%, 0.5%, and 0.9%, while the rest of the preparation method is the same as that of Example 1.

[0023] Raman signal intensity was detected using asymmetric Janus-SERS sensors prepared with the above concentrations, and the results are as follows: Figure 2 As shown, by Figure 2 It can be seen that the asymmetric Janus-SERS sensors prepared with hydroxypropyltrimethylammonium chloride chitosan CCNF concentrations in the range of 0.1% to 0.9% all have strong Raman signals, with the strongest Raman signal when the hydroxypropyltrimethylammonium chloride chitosan CCNF concentration is 0.7%.

[0024] Example 4 Example 4 provides a wearable SERS sensor with an asymmetric Janus structure for the detection of N-acetyl-L-cysteine ​​in tears. The specific method is as follows: The asymmetric Janus-SERS sensor is subjected to different concentrations (10 -7 ~10 -3 The N-acetyl-L-cysteine ​​mixture (M) was soaked for 2 h to construct a linear equation for N-acetyl-L-cysteine. Then, a certain concentration of N-acetyl-L-cysteine ​​was added to the sweat using the standard addition method, and the mixture was detected using an asymmetric Janus-SERS sensor.

[0025] See results Figure 3 B,N-acetyl-L-cysteine ​​at 1601 cm - ¹ This shows a change from 10 -3 M to 10 -7 The linear range of M (R² = 0.99764) and the minimum detectable concentration are 10. -7 M, the limit of detection (LOD) is 0.1012 μM.

[0026] A wearable SERS sensor with an asymmetric Janus structure was used for the detection of uridine in tears: the asymmetric Janus-SERS sensor was compared with different concentrations (10... -7 ~10 -3 Urate (M) was soaked in a mixture for 2 h to construct a linear equation for uridine. Then, a certain concentration of uridine was added to the sweat using the standard addition method, and the mixture was detected using an asymmetric Janus-SERS sensor.

[0027] See results Figure 3 D, uridine at 1587cm - ¹ From 10 -3 M to 10-7 M is linear (R² = 0.99953), and the minimum detectable concentration is 1 × 10⁻⁶. -7 M, LOD is 0.09648 μM.

[0028] A wearable SERS sensor with an asymmetric Janus structure was used for the detection of L-phenylalanine in tears: the asymmetric Janus-SERS sensor was compared with different concentrations (10... -7 ~10 -3 L-phenylalanine (M) was mixed and soaked for 2 h to construct a linear equation for L-phenylalanine. Then, a certain concentration of L-phenylalanine was added to sweat using the standard addition method, and the mixture was detected using an asymmetric Janus-SERS hydrogel sensor.

[0029] See results Figure 3 F,L-phenylalanine at 1003 cm - ¹From 10 -3 M to 10 -7 M is linear (R² = 0.9917), and the minimum detectable concentration is 10. -7 M, LOD is 0.02705 μM.

[0030] The asymmetric Janus-SERS sensor was used for the detection of glycine in tears: the asymmetric Janus-SERS sensor was compared with different concentrations (5 × 10⁻⁶) of glycine. -5 ~5×10 -3 A mixture of glycine (M) was soaked for 2 h to construct a linear equation for glycine. Then, a certain concentration of glycine was added to sweat using the standard addition method, and the mixture was detected using an asymmetric Janus-SERS sensor.

[0031] See appendix for results. Figure 3 H, glycine at 1574 cm - ¹From 5×10 -3 M to 5×10 -5 M is linear (R² = 0.99263), and the minimum detectable concentration is 5 × 10⁻⁶. -5 M, LOD is 61.17 μM.

[0032] Recovery of target analytes in artificial tears: Known concentrations of N-acetyl-L-cysteine, uridine, L-phenylalanine, and glycine were added to artificial tear samples to simulate the tear collection process, and then a peak recovery experiment was performed on an asymmetric Janus-SERS sensor.

[0033] See the appendix for the results. Figure 4The recovery rate of N-acetyl-L-cysteine was between 100.84% and 104.61%, the recovery rate of uridine was between 97.03% and 101.80%, the recovery rate of L-phenylalanine was between 96.49% and 100.66%, and the recovery rate of glycine was between 99.28% and 103.82%.

[0034] Example 5 The asymmetric Janus-SERS sensor prepared by the method of Example 1 was subjected to the following performance tests: (1) In vitro biocompatibility test; S1, cell viability: according to the ISO 10993-5 standard, the asymmetric Janus-SERS sensor film sample (experimental group) was immersed in complete cell culture medium (Dulbecco's modified Eagle's medium containing 10% fetal bovine serum) at a mass-volume ratio of 1:10 (m / v), then 100 μL of the asymmetric Janus-SERS sensor film was used to inoculate L-929 cells, and co-cultured in a 96-well plate at a density of 1 × 10 4 cells / well. L-929 cells were inoculated in blank wells as a control. After 1, 2 and 3 days of culture, CCK-8 solution was added and incubated for another 1.5 h. Finally, the OD value was measured at 450 nm using a microplate reader. The cell viability was calculated according to the following formula:

[0035] S2, live / dead staining: the cell viability at 1, 2 and 3 days was further analyzed using a live / dead cell staining kit, and the cell state was observed under an inverted fluorescence microscope.

[0036] As Figure 5 A is the live / dead cell fluorescence staining image (scale bar is 100 μm) under the co-culture t condition of the L-929 fibroblast control group and the asymmetric Janus-SERS sensor film experimental group; the results are shown in Figure 5 B, compared with the control group, the cell survival rate of the asymmetric Janus-SERS sensor at all time points was more than 95%, indicating that the asymmetric Janus-SERS sensor had no adverse effect on the growth of normal cells and had excellent biocompatibility.

[0037] (2) Antimicrobial performance test: Escherichia coli and Staphylococcus aureus (1 × 10 8 CFU / mL) were co-cultured with the asymmetric Janus-SERS sensor, and each group was set with a bacterial liquid control (only bacterial liquid was added) and a blank control (only medium was added), and placed in a 37°C incubator for 6 hours. The OD600 value was measured to calculate the inhibition rate. The inhibition rate calculation formula is as follows:

[0038] After measuring the OD value, 100 μL of bacterial suspension from each of the blank group, control group, and experimental groups 1 and 2 was transferred to agar plates and incubated at 37°C for 12 hours. Optical images of bacterial colony counts were then captured and recorded. The inhibition rate was as follows: Figure 5 As shown in C, the optical graph of bacterial colony count is as follows: Figure 5 As shown in D; as Figure 5 C and 5D displays show that the asymmetric Janus-SERS sensor has an antibacterial rate of 99.81% against Escherichia coli and 99.72% against Staphylococcus aureus, demonstrating significant antibacterial effects.

[0039] Table 1. Comparison of detection performance of the asymmetric Janus-SERS sensor prepared in Example 1 with other SERS sensors for health monitoring.

[0040] As shown in Table 1, compared with SERS sensors made from other SERS sensor materials, the asymmetric Janus-SERS sensor prepared in Example 1 has an RSD value of 7.63% and good uniformity. The detection limits for NAP and uridine reached 0.1012 μM and 0.09648 μM, respectively, demonstrating extremely high sensitivity and a wide detection range (10). - ³~10 -7 M).

[0041] In summary, Example 4 of this invention demonstrates the fabrication and performance verification of a dual-function asymmetric Janus-SERS sensor. Compared to other SERS sensors, it exhibits higher sensitivity and detection limit, as shown in Table 1. Furthermore, it can be mass-produced using UV polymerization and spin-coating techniques, making it suitable for early glaucoma screening, dynamic monitoring of tear metabolites, and personalized diagnosis and treatment of chronic diseases. As shown in Table 1, this sensor combines high sensitivity (LOD as low as 0.027 μM), uniformity (RSD ≤ 7.63%), biocompatibility (cell viability > 95%), and antibacterial properties (bacteriostatic rate > 99%), demonstrating significant application potential in glaucoma health monitoring.

[0042] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the protection scope of the present invention.

Claims

1. A wearable SERS sensor with an asymmetric Janus structure, characterized in that, The wearable SERS sensor consists of an adhesive layer and a detection layer; the adhesive layer is an acrylic / hydroxypropyltrimethylammonium chloride chitosan hydrogel with a thickness of 53~147mm; the detection layer is gold nanocube-cationic cellulose nanofiber.

2. A method for fabricating a wearable SERS sensor with an asymmetric Janus structure as described in claim 1, characterized in that, Includes the following steps: (1) Preparation of adhesive layer: Acrylic acid and hydroxypropyltrimethylammonium chloride chitosan are mixed, crosslinking agent and photoinitiator are added, and the mixture is stirred thoroughly to prepare a prepolymer solution. The prepolymer solution is transferred to a mold and irradiated with ultraviolet light to form an acrylic acid / hydroxypropyltrimethylammonium chloride chitosan hydrogel adhesive layer. (2) Preparation of the detection layer: Take HAuCl4 solution, hexadecyltrimethylammonium bromide solution and ultrapure water and stir evenly. Then add NaBH4 solution and mix evenly. Let stand to prepare gold seed solution. After diluting the gold seed solution, add growth solution made of ultrapure water, hexadecyltrimethylammonium bromide, HAuCl4 and ascorbic acid. Let stand to generate gold nano cubes. After purification, obtain gold nano cube solution. Centrifuge and concentrate the gold nano cube solution to remove hexadecyltrimethylammonium bromide. Add cationic cellulose nanofibers and mix to prepare gold nano cube-cationic cellulose nanofiber detection layer. (3) Janus structure assembly: The gold nanocube-cationic cellulose nanofiber detection layer was spin-coated onto the surface of the acrylic acid / hydroxypropyltrimethylammonium chloride chitosan hydrogel adhesive layer to form a wearable SERS sensor with an asymmetric Janus structure.

3. The method for fabricating a wearable SERS sensor with an asymmetric Janus structure according to claim 2, characterized in that, The mass ratio of acrylic acid to hydroxypropyltrimethylammonium chloride chitosan is 2:

1.

4. The method for fabricating a wearable SERS sensor with an asymmetric Janus structure according to claim 2, characterized in that, The concentration of the hydroxypropyltrimethylammonium chloride chitosan is 1% to 3%.

5. The method for fabricating a wearable SERS sensor with an asymmetric Janus structure according to claim 2, characterized in that, The crosslinking agent is N,N'-methylenebisacrylamide, with a concentration of 2%, accounting for 2.5% of the mass of acrylic acid.

6. The method for fabricating a wearable SERS sensor with an asymmetric Janus structure according to claim 2, characterized in that, The photoinitiator is 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, with a concentration of 1%, accounting for 2.5% of the mass of acrylic acid.

7. The method for fabricating a wearable SERS sensor with an asymmetric Janus structure according to claim 2, characterized in that, The concentration of the cationic cellulose nanofibers is 0.1% to 0.9%.

8. Application of a wearable SERS sensor with an asymmetric Janus structure in the field of non-invasive tear metabolite monitoring.

Citation Information

Patent Citations

  • Preparation method and application of ultrathin skin / glove-based wearable SERS sensor

    CN114034682A

  • LoC-SERS platform for detecting Parkinson's disease marker and application

    CN118109563A